2021
DOI: 10.1177/23409444211002521
|View full text |Cite
|
Sign up to set email alerts
|

High-performance work practices, socioemotional wealth preservation, and family firm labor productivity*

Abstract: Despite growing research on the effect of high-performance work practices (HPWPs) on family firm performance, the implications of socioemotional wealth (SEW) preservation remain ambiguous. This stems from SEW preservation being used primarily as an explanatory construct and assessed indirectly rather than directly in empirical studies. To address this research gap, we draw upon organizational control and signaling theories to determine the “true” interaction between HPWPs and SEW preservation for labor product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 134 publications
2
19
0
Order By: Relevance
“…In this vein, we extend the empirical exploration of SEW and its impact on financial performance (Berrone et al, 2012;Craig and Newbert, 2020;Debicki et al, 2017) and the mediating role that HRM choices play in that relationship (G omez-Mej ıa et al, 2011). As such, we contribute to the debate on family firm heterogeneity (Chua et al, 2012) and the effectiveness of HRM policies in the family business context (Hern andez-Perlines et al, 2021;Neckebrouck et al, 2018). Second, we also contribute to the HRM literature by adopting an alternative theoretical approach to provide a better understanding of vertical fit in HRM (Kehoe, 2021).…”
Section: Ijebr 281mentioning
confidence: 65%
See 2 more Smart Citations
“…In this vein, we extend the empirical exploration of SEW and its impact on financial performance (Berrone et al, 2012;Craig and Newbert, 2020;Debicki et al, 2017) and the mediating role that HRM choices play in that relationship (G omez-Mej ıa et al, 2011). As such, we contribute to the debate on family firm heterogeneity (Chua et al, 2012) and the effectiveness of HRM policies in the family business context (Hern andez-Perlines et al, 2021;Neckebrouck et al, 2018). Second, we also contribute to the HRM literature by adopting an alternative theoretical approach to provide a better understanding of vertical fit in HRM (Kehoe, 2021).…”
Section: Ijebr 281mentioning
confidence: 65%
“…We focus on these policies because they are considered a well-known coordinated bundle of economically oriented human resource (HR) policies that may help improve family firm performance (Bello-Pintado and Garc es-Galdeano, 2019; Dekker et al, 2015;Posthuma et al, 2013). Despite this relevance, there is scant empirical evidence about how HPWPs mediate the relationship between family influence, in terms of SEW preservation and firm financial performance (Hern andez-Perlines et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, in the study titled "Women ownership as a form of leadership: The role of context in understanding its effects on financial performance," Orozco Collazos and Botero (2024) choose as study context Colombia, a country whose society is highly masculine and where there exits not laws or incentives that promote gender equality in the private sector (Orozco Collazos & Baldrich, 2020;Orozco Collazos & Botero, 2024). Specifically, Orozco Collazos and Botero ( 2024) analyze the relationship between women ownership and financial performance of Colombian private small and mediumsized enterprises (SMEs) and the moderating role of a context as unique as the family firm (Berrone et al, 2012;Domańska et al, 2023;Hernández-Linares et al, 2023;Hernández-Linares & López-Fernández, 2020) in this relationship. Authors explore these relationships by using multiple regression analysis with data retrieved from secondary databases.…”
Section: Articles In This Special Issuementioning
confidence: 99%
“…From the family business literature, a stream of research has shown that HR policies, including performancebased compensation, constitute a concrete manifestation of family influence (Hernández-Linares et al, 2021;Peláez-León & Sánchez-Marín, 2023;Steijvers et al, 2017). More specifically, when there is more of the owning family in management, performance-based compensation policies are better accepted due to the family's desire to express a sense of consistency and fairness for all employees (Steijvers et al, 2017).…”
Section: O R G a N I Z A T I O N A L C U L T U Re A N D Compensation ...mentioning
confidence: 99%